2017
DOI: 10.4102/curationis.v40i1.1578
|View full text |Cite
|
Sign up to set email alerts
|

A profile of perceived stress factors among nursing staff working with intellectually disabled in-patients at the Free State Psychiatric Complex, South Africa

Abstract: IntroductionNursing staff working with intellectually disabled in-patients experience unique stress factors that can influence their personal well-being and work performance.ObjectivesTo compile a profile of stress factors experienced by nursing staff working with intellectually disabled in-patients at the Free State Psychiatric Complex (FSPC).MethodsThis descriptive study included 89 nursing staff members from this environment. A questionnaire was used to collect socio-demographic information and determine pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…Apart from morally distressful situations and secondary traumatic stress syndrome, emotional exhaustion has also been identified as a job-related hazard for MHNs. Studies in MHNs have reported association between emotional exhaustion and several health outcomes, including low self-reported somatic health level [ 54 , 55 ], anxiety and depressive symptoms [ 56 , 57 ], or higher risk of health-threatening behaviours, such as tobacco smoking [ 58 ] or consumption of alcohol [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from morally distressful situations and secondary traumatic stress syndrome, emotional exhaustion has also been identified as a job-related hazard for MHNs. Studies in MHNs have reported association between emotional exhaustion and several health outcomes, including low self-reported somatic health level [ 54 , 55 ], anxiety and depressive symptoms [ 56 , 57 ], or higher risk of health-threatening behaviours, such as tobacco smoking [ 58 ] or consumption of alcohol [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main work-related stressors encountered by MHNs, possibly associated with psychosocial and job-related hazards, may be grouped into two categories [ 36 , 51 , 55 , 59 , 60 ]: those stressors related to the therapeutic relationship and the nursing process of care, namely, challenging behaviours by patients and their family members, physical and verbal violent behaviour towards clinicians by patients, patients' suicidal behaviour, nonadherence to therapy, and insufficient time to provide optimal care, and those related to the working context, that is, poor staffing, inadequate referral systems, heavy workload, insufficient resources, type of working setting (community versus hospital settings), and uncertainty of employment.…”
Section: Introductionmentioning
confidence: 99%
“…15 For health care providers in remote and border areas in developed countries, limited basic education and skill training also resulted in their occupational stress. 16,17 However, in developing or undeveloped countries, limitations of professional knowledge and skills to perform routine tasks, [18][19][20] nursing care, operating upto-date medical equipment, 21 and communication 22,23 are the primary stressors among health care providers.…”
mentioning
confidence: 99%
“…O občutenju stresa na delovnem mestu poroča približno tretjina medicinskih sester. Na delovnem mestu medicinske sestre so najpogostejši stresorji preobilica dela, neudeležba v procesu sprejemanja odločitev, prenizko plačilo in slaba podpora nadrejenih (Conradie et al, 2017;Lee & Kim, 2020). Stalni stres lahko vodi do izgorelosti, ki negativno vpliva tako na medicinsko sestro kot tudi na bolnike.…”
Section: Izgorelost V Zdravstveni Negiunclassified